Degradation of patulin in fruit juice by a lactic acid bacteria strain Lactobacillus casei YZU01. (June 2020) - Zheng, Xiangfeng; Wei, Wanning; Rao, Shengqi; Gao, Lu; Li, Huaxiang; Yang, Zhenquan
Abstract: Patulin, a secondary metabolite produced by fungi, such as Aspergillus, Penicillium, and Byssochlamys, is highly toxic to bacteria and plants and exerts serious threat to human and animal health. The use of beneficial microbes shows good effect and application prospects in removing mycotoxins. As a widely used biological control agent, lactic acid bacteria (LAB) can remove mycotoxins from foodstuff. In this research, a LAB strain that can degrade patulin, namely, Lactobacillus casei YZU01, was screened. The physiological mechanism of patulin degradation by L. casei YZU01 was investigated. L. casei YZU01 mainly degraded patulin by secreting extracellular metabolites, and its cell wall also absorbed patulin. Furthermore, L. casei YZU01 was applied for the removal of patulin in raw apple juice (RAJ) or raw pear juice (RPJ). Patulin (10 μg/mL) in RAJ or RPJ was completely degraded by L. casei YZU01 after 36 h of incubation, and patulin in commercialized apple or pear juice products was degraded after 48 h of incubation after treatment with L. casei YZU01. Results indicated the potential of L. casei YZU01 in dealing with patulin contamination in food industries. Highlights: Lactobacillus casei YZU01 can degrade patulin. L. casei YZU01 degrade patulin by secreting extracellular metabolites. L. casei YZU01 shows good effect to remove patulin from foodstuff.